A contribuição de Duns Scotus para uma espiritualidade ecológica - Silva, Adelmo Francisco Gomes da (Revista eclesiástica brasileira, 2008)
Duns Scotus presents us with a God as infinite love who makes Himselfhuman not necessarily in virtue of sin butfi'eely, because He wants to be loved in view ofhis externai self and in particular in view ofhis supre- me work, Jesus Christ. A God who, in virtue of sin, should not necessarily have suffered and died on the cross, but who historically undertook the cause of justice in the hope of attracting our love further through this. Conside- ring the ecological challenges and the threat ofextinction ofhuman lifie on earth, such a view of God certainly gives meaning to mankinds millenary history, a guaranteed hope oflife and amidst so much pain, thepossibility to manifest love.